Overview of Chassis Domain Control System Architecture, Algorithms, and Verification Techniques: -- A Survey of Chassis Domain Control System Architecture, Algorithms, and Verification Techniques for Autonomous Vehicles - Xie , Ke (International Journal of Mechanical and Electrical Engineering, 2026)
This work systematically reviews the current status and development trends of autonomous vehicle chassis domain control systems across three dimensions: architecture, algorithms, and verification techniques. During the transformation toward intelligent vehicles, the limitations of traditional distributed electronic/electrical architectures in enhancing advanced autonomous driving capabilities have become apparent, prompting both industry and academia to shift focus toward the evolution of centralized domain control architectures. This study delves into the technical drivers and challenges underlying the evolution of chassis domain control systems from distributed to domain-centralized architectures. Building upon this foundation, it further explores the emerging trend toward zonal architecture. The study emphasizes hardware-software co-design strategies compliant with AUTOSAR standards. Through in-depth investigation and comprehensive evaluation, it conducts a holistic comparative analysis of traditional control methods—such as model-based predictive control and sliding mode control—alongside data-driven deep reinforcement learning strategies, examining their performance limits and application prospects within integrated vehicle chassis control systems. Finally, it systematically summarizes verification methodologies based on high-fidelity simulation (e.g., CARLA) and hardware-in-the-loop testing. This research aims to fill the current gap in integrating system-level architecture theory, providing a comprehensive technical blueprint and theoretical foundation for developing next-generation high-performance, high-safety intelligent chassis control systems.